2015
DOI: 10.1182/blood-2014-08-597419
|View full text |Cite
|
Sign up to set email alerts
|

Defective PDI release from platelets and endothelial cells impairs thrombus formation in Hermansky-Pudlak syndrome

Abstract: Key Points Hermansky-Pudlak syndrome exhibits impaired granule exocytosis and PDI secretion that contribute to its associated bleeding disorder. Endothelial cells deficient in HPS6 show defective secretion of granules, including Weibel-Palade bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
2
51
1
1
Order By: Relevance
“…Poole and colleagues showed that ADP addition overrides much of the α-granule secretion defect [72]. These data underline the fact that dense granule secretion deficiency precipitates defects in α-granule and lysosome release; a point that has been noted by others [73, 74]. Thus, the autocrine signaling from released ADP plays a critical role in modulating α-granule and lysosome release.…”
Section: Snare Regulatory Proteinsmentioning
confidence: 78%
“…Poole and colleagues showed that ADP addition overrides much of the α-granule secretion defect [72]. These data underline the fact that dense granule secretion deficiency precipitates defects in α-granule and lysosome release; a point that has been noted by others [73, 74]. Thus, the autocrine signaling from released ADP plays a critical role in modulating α-granule and lysosome release.…”
Section: Snare Regulatory Proteinsmentioning
confidence: 78%
“…59 The core comprises tightly packed, degranulated platelets encased in fibrin. 59 ADP released from dense granules regulates a-granule secretion, [60][61][62] forming dense regions that stabilize the platelet aggregate. 63 Concomitant release of polyP with ADP from dense granules suggests that it may be retained in these low-solute transport areas.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets and endothelial cells from HPS mice are deficient in the secretion of PDI. 44 Furthermore, infusion of recombinant PDI reverses the thrombus formation defect in HPS mice (S. H. Kim and B. Furie, unpublished observations, 2013). Whether recombinant PDI shortens bleeding times in mice has not yet been determined.…”
Section: Thiol Isomerases In Coagulopathymentioning
confidence: 99%
“…41 Several other groups subsequently demonstrated that thiol isomerases traffic to secretory granules/membrane systems and are released from platelets in an activation-dependent manner. 36,[42][43][44][45] Kim et al showed that platelets lacking PDI have reduced activation-dependent aggregation. 46 Platelet surface PDI has been postulated to modulate a IIb b 3 function, 47 Thiol isomerases have also been found on the surface of the endothelium.…”
Section: Vascular Thiol Isomerasesmentioning
confidence: 99%